Pengaruh Kedisiplinan dan Komitmen pada Tugas Terhadap Pemahaman Konsep Matematika Siswa - Lutur, Elen Marta; Sajiman, Supardi Uki (Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
ABSTRACT: The purpose of this study was to determine the effect of discipline and commitment to the task of understanding students' mathematical concepts. In this study, survey research methods were used. Multiple regression analysis was performed with ANOVA statistics (variance analysis). The results of the study concluded: (1) There is no significant direct influence in the discipline of understanding Mathematical concepts with t-count = 1 082 <1,980. (2) There is a significant direct effect of commitment to the task of understanding mathematical concepts with t-count = 2,248> 1,980. (3) There is a significant direct effect of discipline on commitment to the task is t-count = 3.936> 1.980. (4) There is an insignificant indirect influence in the discipline of understanding mathematical concepts through commitment to the task is t-count = 0.936 <1.980. Efforts to improve understanding of mathematical concepts in students are carried out with discipline and commitment to the tasks students have in the teaching and learning process.  Keywords: Discipline, Commitment to tasks, Understanding of Mathematical Concepts.